Review of Microplastic Pollution in Indonesian Waters - Frinsis Warmansyah; Serly Mutia Sari; Siska Wardeni; Eni Kamal; Isril Berd; Abdul Razak (Science and Environmental Journal for Postgraduate, 2023)
Mismanaged plastic wastes still become main environmental problem in many countries. It also believed as the root of many environmental problem today faced by both advanced and develop countries, like Indonesia. Microplastics polluted the aquatic environment of Indonesia today mainly come from mismanaged plastic wastes (secondary), but both of the primary and secondary microplastics exist in Indonesian water. This paper reviews microplastic pollution in Indonesian water focused on two main topics, namely the characteristics of microplastics in Indonesian waters and their sources and effects of the presence of microplastics on aquatic organisms. This article was compiled using secondary data consisting of various data and papers, materials obtained from various sources of relevant and reliable official publications that are closely related to the microplastic pollution in Indonesian waters. These findings were then analyzed in an explanatory descriptive manner to provide an overview of characteristics and the sources of microplastics in Indonesian waters and how microplastics affect aquatic ecosystems. It is hoped that this will provide an opportunity to address this issue more effectively.